CTHRC1 Derived From Cancer‐Associated Fibroblasts Promotes Pancreatic Cancer Progression and Metastasis via the LIF‐STAT3 Pathway - Hang Yin; Yue Pan; Zhuang Li; Yong Liu; Jiatong Chen; Xin Chen; Chengfei Zhang; Feng Zhu; Chunzhao Yu (Cancer Medicine)
ABSTRACT Background Collagen triple helix repeat containing 1 (CTHRC1) is a secreted protein involved in tissue remodeling and fibrotic processes, which also suggests emerging roles in cancer. Studies have shown that it is mainly expressed in the outer membrane fibroblasts of injured arteries and in the neointimal smooth muscle cells, where it promotes cell migration and tissue damage repair. However, the regulatory role of CTHRC1 as a tumor microenvironment factor in pancreatic cancer is not well understood. Methods We employed multi‐omics analysis combined with cellular and animal experiments to examine the association between CTHRC1 and the LIF/STAT3 pathway in pancreatic cancer clinical specimens. Using AsPC‐1/PANC‐1 and other cell lines, we conducted proliferation, migration, invasion, and signaling pathway studies, and elucidated the regulatory mechanism of CTHRC1 through genetic interventions and STAT3 inhibitors. Results In this study, we found that CTHRC1 is highly expressed in the cancer‐associated fibroblasts (CAFs) of pancreatic cancer and is associated with poor prognosis in patients. Functionally, we observed that CTHRC1 in CAFs promotes the proliferation, migration, and invasion of pancreatic cancer cells both in vitro and in vivo. In mechanistic studies, RNA sequencing revealed that CTHRC1 promotes the proliferation and migration of pancreatic cancer cells through the LIF‐mediated STAT3 axis. Conclusion These findings reveal the role of CTHRC1 in CAFs in pancreatic cancer, suggesting that it is an attractive therapeutic target and tumor marker. This study uncovers the biological mechanism of CTHRC1 in CAFs in pancreatic cancer, providing new strategies for the treatment of pancreatic cancer.